Dielectric Materials for Thin-Film-Based Optical Communications Filters - Sargent, Robert B.; O'Brien, Nada A. (MRS bulletin, 2003)
Explosive growth in the fiber-optic telecommunications infrastructure during the past decade has driven noteworthy advances in thin-film-based optical interference filter technology. In particular, the widespread deployment of wavelength-division multiplexing (WDM), a means of increasing the communication capacity of an optical fiber by utilizing more than one wavelength of light, has motivated significant improvements in bandpass filter performance. A common requirement is for filters that combine or separate wavelengths spaced 100 GHz (0.8 nm) apart. The foundation for these recent breakthroughs has been laid by the development of optical coating technology over the past century. This article reviews the materials and processes used in the production of thin-film-based optical communications filters.